Amanah Dalam Perspektif Hadis - Reza Pahlevi Dalimunthe (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2016)
Amanah is God's gift to the sky but the sky is not able to carry it, only humans who dared to accept the mandate it. Amanah, Hugo is a noble trait that has been attached to the Apostles themselves. The opposite of the treasonous, because treasonous is one of the signs of hypocrisy and Islam strictly forbid it. Amanah in reality is not so simple, because by their mandate means no loading or demand for the concerned to realize. Various methods were used to reveal the meaning and intent of the terms of the trust both in the hadith. From there will appear a comprehensive understanding of the mandate. This article seeks to unravel the mandate and matters related to the mandate covers and Nature of Amanah, Criteria Amanah Amanah based on the Hadith. Not only as an perspectife religion but also the effort to achieve skill academic development.